Final de la Vida: Una Mirada de la Eutanasia y el Suicidio como Opciones (Hilo Analítico, 2021)
Perhaps talking about life and death is one of the most confusing topics, the repressed ideations as a resultof domestic violence are currently a tragicomedy, but by joining the points of existence now everything can beseen more clearly and before this, the end Life has two enormous perspectives, one such as Suicide and aparticular view such as Euthanasia, initially according to the World Health Organization (WHO), 900,000 suicidesare committed each year in the world, a rate of 16 per 100,000 inhabitants. , somewhat disturbing indicators,we will not know if death is a way out from pain or those situations where unresolved conflicts are reflectedin melancholy